2001
DOI: 10.1042/0264-6021:3570709
|View full text |Cite
|
Sign up to set email alerts
|

A three-step kinetic mechanism for selective inhibition of cyclo-oxygenase-2 by diarylheterocyclic inhibitors

Abstract: Cyclo-oxygenase (COX) enzymes are the targets for non-steroidal anti-inflammatory drugs (NSAIDs). These drugs demonstrate a variety of inhibitory mechanisms, which include simple competitive, as well as slow binding and irreversible inhibition. In general, most NSAIDs inhibit COX-1 and -2 by similar mechanisms. A unique class of diarylheterocyclic inhibitors has been developed that is highly selective for COX-2 by virtue of distinct inhibitory mechanisms for each isoenzyme. Several of these inhibitors, with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 40 publications
8
50
0
Order By: Relevance
“…S1). We also confirmed that, unlike the situation with COX-2, celecoxib is a freely reversible, competitive inhibitor of COX-1 (24). The fact that celecoxib is a freely reversible inhibitor of COX-1 suggests that celecoxib must bind to both monomers of COX-1 to cause enzyme inhibition (10).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…S1). We also confirmed that, unlike the situation with COX-2, celecoxib is a freely reversible, competitive inhibitor of COX-1 (24). The fact that celecoxib is a freely reversible inhibitor of COX-1 suggests that celecoxib must bind to both monomers of COX-1 to cause enzyme inhibition (10).…”
Section: Resultssupporting
confidence: 65%
“…Inhibition of COX-2 by many nsNSAIDs and by coxibs including celecoxib has at least two phases. The first is a very rapid, second-order kinetic interaction, and this is followed by a much slower, firstorder conformational rearrangement (9,(21)(22)(23)(24). The intrinsic binding affinity of inhibitors for COXs can be estimated by measuring "instantaneous" inhibition that occurs when enzyme, substrate, and inhibitor are mixed without preincubating the inhibitor and enzyme (22).…”
Section: Resultsmentioning
confidence: 99%
“…Why this was observed is not certain. It is known that the mechanism by which vitamin D and celecoxib influence PGE2 production is different, the former limiting the production of COX2 (2) and the latter directly inhibiting COX2 (5). If validated, our findings suggest that the preferred treatment to decrease breast cancer risk depends on risk status.…”
Section: Discussionsupporting
confidence: 55%
“…A more detailed kinetic study indicates the existence of a three-step kinetic mechanism for the selective inhibition of COX-2 by celecoxib. 101 The reversible association of diaryl heterocycle inhibitors with COX, measured by following the inhibition of consumption of molecular oxygen as arachidonic acid is oxygenated by COX-2, comprises two steps that may or may not appear kinetically distinct, depending on the relative magnitudes of the rate constants. 101 The selectivity of the inhibitors for COX-2 is derived from the contribution of a third pseudoirreversible step that leads to a tightly bound complex.…”
Section: Iii4 Diaryl Heterocycles (Sulfonamides and Methyl Sulfones)mentioning
confidence: 99%
“…101 The reversible association of diaryl heterocycle inhibitors with COX, measured by following the inhibition of consumption of molecular oxygen as arachidonic acid is oxygenated by COX-2, comprises two steps that may or may not appear kinetically distinct, depending on the relative magnitudes of the rate constants. 101 The selectivity of the inhibitors for COX-2 is derived from the contribution of a third pseudoirreversible step that leads to a tightly bound complex. The difference in the rate constants for association of diaryl heterocycles with COX-1 and COX-2 does not correlate to the differences in selectivity.…”
Section: Iii4 Diaryl Heterocycles (Sulfonamides and Methyl Sulfones)mentioning
confidence: 99%